Enhancing the Accuracy of Mobile Geo Targeting - Dmitry Sergeevich Silnov (International Journal of Electrical and Computer Engineering (IJECE), 2016)
SMS advertising companies use mobile phone numbers to send its own content. Geo targeting can improve advertising possibilities. New approach of mobile numbers geo targeting discovered and used in Russia. That approach can be used not only in Russia, but its universal for any country. For Russian geo targeting used site avito.ru for attaching mobile to selected area in city.